Evaluation of the leishmanicidal activity of plants used by Peruvian Chayahuita ethnic group - Estevez Y. (2007)
The authors gratefully acknowledge the financial assistance of CONCYTEC from Peru and DSF-IRD (JEAI) from France. We express our thanks to members of the Chayahuitas community who were willing to share with us their knowledge about medicinal plants. The authors are grateful to Candy Ruiz from LID-UPCH, for technical assistance in plants extractions.